A Practical Approach for Quantifying Country Risk on the Ukrainian Stock Market - Khomenko, Ya.V.; Molchanov, O.I.; Sheyka, K.S. (Економічний вісник Донбасу, 2013)
This article represents the theoretical basis of country risk evaluating for emerging markets. It also contains the results of testing modified CAPM which include country risk premium for Ukrainian stock market. The study is based on data from the Ukrainian Stock Exchange and UX index for 2009 - 2011.